2009
DOI: 10.1055/s-0029-1217048
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Reactions of 2-Methylimidazoline and 1,2-Dimethylimidazoline with Various Benzoyl Chlorides

Abstract: The reactions of 2-methylimidazoline with excess benzoyl chlorides under mild conditions generated N,N¢-diacyl-b-keto cyclic ketene-N,N¢-acetals. Conversely, the corresponding reactions of 1,2-dimethylimidazoline under the same conditions stereoselectively formed the ring-opened (Z)-vinyl benzoates. The latter reactions feature the formation of carbon-carbon bonds, carbonnitrogen bonds, and carbon-oxygen bonds in one sequential cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Recently, reactions of 2-methylimidazoline, 2-methyl-1,4,5,6-tetrahydropyrimidine, and 1,2-dimethyl-1,4,5,6-tetrahydropyrimidine were reported to give various cyclic and acyclic products via cyclic ketene N,N¢-acetals when treated with aroyl chlorides in the presence of a base. [27][28][29] Also, 2-methylimidazoline, 2-methylimidazole, and 2-methylbenzimidazole formed both polycyclic and acyclic products with diacid chlorides through cyclic ketene acetal intermediates in the presence of a base. 30,31 Thus, we envisaged that analogous aromatic oxazoles and thiazoles with a 2-methyl group might undergo similar reactions with acid chlorides to those in Scheme 2.…”
Section: Scheme 1 Resonance Structures Of Cyclic Ketene Acetalsmentioning
confidence: 99%
“…Recently, reactions of 2-methylimidazoline, 2-methyl-1,4,5,6-tetrahydropyrimidine, and 1,2-dimethyl-1,4,5,6-tetrahydropyrimidine were reported to give various cyclic and acyclic products via cyclic ketene N,N¢-acetals when treated with aroyl chlorides in the presence of a base. [27][28][29] Also, 2-methylimidazoline, 2-methylimidazole, and 2-methylbenzimidazole formed both polycyclic and acyclic products with diacid chlorides through cyclic ketene acetal intermediates in the presence of a base. 30,31 Thus, we envisaged that analogous aromatic oxazoles and thiazoles with a 2-methyl group might undergo similar reactions with acid chlorides to those in Scheme 2.…”
Section: Scheme 1 Resonance Structures Of Cyclic Ketene Acetalsmentioning
confidence: 99%
“…8 Most recently, divergent reactions have been observed in the reactions of aroyl chlorides with 2-methyl-4,5-dihydro-1Himidazole (1) and 1,2-dimethyl-4,5-dihydro-1H-imidazole (2; Scheme 2). 9 Scheme 2 Divergent reactions of aroyl chlorides with 2-methyl-4,5dihydro-1H-imidazole (1) or 1,2-dimethyl-4,5-dihydro-1H-imidazole (2) This suggested that the N-substituents have a decisive effect on the reactivity of the five-membered ketene N,N¢acetals formed in these reactions. To investigate the effects of the ring size on the cyclic ketene N,N¢-acetals, we sought to expand this chemistry to the six-membered analogues of these compounds.…”
Section: Scheme 1 Basic Structure Of Ketene Acetals and The Origin Ofmentioning
confidence: 99%
“…To investigate the effects of the ring size on the cyclic ketene N,N¢-acetals, we sought to expand this chemistry to the six-membered analogues of these compounds. We therefore examined the reactions of aroyl chlorides with 2-methyl-1,4,5,6-tetrahydropyrimidine (5) and 1,2-dimethyl-1,4,5,6-tetrahydropyrimidine (9). The reaction of pyrimidine 5 with excess of an aroyl chloride in refluxing tetrahydrofuran-triethylamine mixtures did not generate the expected triaroylation product 7 (Table 2).…”
Section: Scheme 1 Basic Structure Of Ketene Acetals and The Origin Ofmentioning
confidence: 99%
“…Cyclic ketene acetals are a highly reactive class of compounds with significant synthetic potential [1]. The exocyclic methylene carbons in each are nucleophilic due to conjugation with the respective heteroatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Pittman and coworkers have extensively explored the synthetic potential of many cyclic ketene acetal species [1,2] with both mono-and dielectrophiles, discovering a rich variety of reactions ranging from tandem cyclizations [1,3,4], bis additions followed by ring-opening and re-closure isomerizations [2], arylvinyl ester formation [1,4,5], ''push-pull'' compound formation [6,7], new heterocyclic ring and fused ring formation [2,3,6,8,9], ring-opening reactions [10], ring-retained polymerization and copolymerizations [11][12][13][14][15][16][17][18][19][20], spirobicyclic ring formation [21], and stereoselective radical cyclizations [21,22]. However, all of these studies have been carried out only on five-; six-; and seven-membered ring systems .…”
Section: Introductionmentioning
confidence: 99%